A construção discursiva da mulher brasileira em Retrato falado, quadro humorístico do programa de televisão Fantástico da Rede Globo - Oliveira, Christiane Maria da Bôa Viagem (2009)
Found on the semiotic theory of A. J. Greimas, this research work investigates the humorous sketch Retrato Falado which is part of tradicional Sunday TV program, Fantástico (Rede Globo). It aims and identifies the discursive construction of the brazilian woman simulacrum. This study is based on 15 episodes which was selected and joined together in DVD, published in 2005 by Rede Globo, Retrato Falado s addresser. Retrato Falado was exhibited for seven years and during this time, many episodes made it biggest peak audience of Fantástico. It means that Retrato Falado had a specific public further the audience of that TV program. Transmited weekly, it presented as a humorous sketch about feminine day after day. The analysis of this sketch pointed us to themes about woman s daily universe and how these are showed to the audience. Then we understand that Retrato Falado shows itself with a singular and signifcative discurse construction of brazilian woman and it is organized from testimonies of women from many brazilian places who tell a cheerful history about their own lifes. Maintaining good humour, the history is transformed in a TV product from stage reports inserte between woman s testimony, in addition to grafics about statistics and curious datas. What with these histories of feminine daily facts, Retrato Falado presents roles of brazilian woman being , constructing then its simulacrum. The enunciator proceedings for discursive construction are done by semiotic system and process syncretism once the TV audiovisual is used to manipulate the addressee, which also is guided to sensitization and, for the estese, a condition to feel the meaning, is coordinated to humorous ludic actions. From studies of the french semiotician Eric Landowski, we could aim to interactions logics established between addresser and addressee which occur by manipulation and ajustement regimes, interactions that assemble and mix while lively experience gain visibility in this sketch. Retrato Falado reiterates and reaffirms the woman s doing in the society and its importance inside this world s vision presented. This woman still presents herself submissive by a masculine power that is assumed by an association of many addressers: Rede Globo, society and woman. This work makes a profound study of media, in particular, television media which is orientated for consolidate axiology, role which revitalizes social structures and behaviors